2003
DOI: 10.1038/sj.jhh.1001538
|View full text |Cite
|
Sign up to set email alerts
|

Shifting trends in the pharmacologic treatment of hypertension in a Nigerian tertiary hospital: a real-world evaluation of the efficacy, safety, rationality and pharmaco-economics of old and newer antihypertensive drugs

Abstract: The current prescription patterns for essential hypertension and the efficacy, safety, tolerability and costeffectiveness of the newer antihypertensive drugs were evaluated in Nigerian patients. The findings were compared with that of a previous study conducted in the same tertiary hospital 10 years earlier. A crosssectional evaluation of blood pressure (BP) control in a hypertension clinic was undertaken among 150 Nigerian patients aged 61712 years (55% females), with a duration of treatment on a particular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
44
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 23 publications
6
44
0
1
Order By: Relevance
“…The choice of diuretic as the first line antihypertensive drug is consistent with other reports from Nigeria, 10,13,14 and in compliance with the current national 15 and JNC VII guidelines. 8 However, contrary to the traditional recommendations in most guidelines including the report of Antihypertensive and Lipid-Lowering treatment to prevent Heart Attack Trial (ALLHAT), 16 calcium channel blocker was found to lower blood pressures more than diuretic when both were used as monotherapy.…”
Section: Discussionsupporting
confidence: 73%
“…The choice of diuretic as the first line antihypertensive drug is consistent with other reports from Nigeria, 10,13,14 and in compliance with the current national 15 and JNC VII guidelines. 8 However, contrary to the traditional recommendations in most guidelines including the report of Antihypertensive and Lipid-Lowering treatment to prevent Heart Attack Trial (ALLHAT), 16 calcium channel blocker was found to lower blood pressures more than diuretic when both were used as monotherapy.…”
Section: Discussionsupporting
confidence: 73%
“…7,8 The observed trend regarding CCBs predominating as preferred drug overall is similar to reports from other hospitals with a primarily black population. 5 The low rate of normotension achieved by our patients on CCB monotherapy compared with other studies could be partially ascribed to a myriad of generic forms of nifedipine available in the market, the standard and efficacy of which cannot be guaranteed. Although diuretics were not commonly prescribed as first line monotherapy, the percentage of patients with controlled hypertension was highest in this group and also in the group with diureticbased regimen.…”
mentioning
confidence: 67%
“…There is a favourable disposition to combination therapy in recent years particularly in patients with more difficult to control BP (often encountered in tertiary or referral settings). 5 There is rational justification for such therapy because the multifactorial nature of hypertension is addressed, BP control and achievement of target BP tends to be better, and the risk of side effects owing to use of maximal doses of monotherapeutic agents is reduced. Furthermore, hypertension in black people runs an aggressive course and control is achieved with multiple drug therapy rather than monotherapy.…”
mentioning
confidence: 99%
See 2 more Smart Citations